Stabilized Nitrogen Fertilizers and Application Rate Influence Nitrogen Losses under Rainfed Spring Wheat. (1st September 2015) - Thapa, Resham; Chatterjee, Amitava; Johnson, Jane M.F.; Awale, Rakesh
Abstract : Nitrogen losses associated with fertilizer application have negative economic and environmental consequences, but urease and nitrification inhibitors have potential to reduce N losses. The effectiveness of these inhibitors has been studied extensively in irrigated but not in rainfed systems. This study was conducted at Glyndon, MN, under rainfed conditions to assess the impact of urease and nitrification inhibitors on NH3 volatilization, N2 O emissions, and NO3 − concentrations below the spring wheat ( Triticum aestivum L.) rooting zone. Urea (U), urea with urease and nitrification inhibitors (SU), and urea with nitrification inhibitor only (UI) were applied at 146 and 168 kg N ha −1 along with the control treatments. Cumulative NH3 volatilization was reduced by 26%, N2 O emissions measured 18 d after planting were reduced by 50% with SU, but no significant reduction was observed with UI compared to U. We did not observe a significant effect of higher N rate on N2 O emissions, but lower N application rate (146 kg N ha −1 ) significantly reduced NH3 volatilization by 26% compared to 168 kg N ha −1 . Nitrate concentration below the rooting zone was reduced by applying N at lower rate and also through the use of SU and UI instead of U. Soil inorganic N intensity was significantly related with cumulative N2 O emissions. Nitrogen source and rate did not influence grain yield and protein content. This single‐growing season study under rainfed conditions suggests that fertilizer N‐stabilizers can be successfully used to minimize N losses without compromising grain yield and protein content.